Applicability of BIM-IoT-GIS integrated digital twins for post occupancy evaluations - Tripathi, Ishan; Froese, Thomas M.; Mallory-Hill, Shauna (Frontiers in Built Environment, 2023)
Post Occupancy Evaluations (POE) provide a systematic methodology for determining the performance gap between expected and actual performance. Monitoring quality of the indoor environment is essential for understanding building performance in relation to occupant health, wellbeing, and comfort. Because of the global COVID 19 pandemic, researchers faced numerous issues accessing the building for collecting data and making spot measurements of the indoor environment. Technologies such as Building Information Modeling (BIM), Internet of Things (IoT), and Geographical Information Systems (GIS) have the potential to address existing challenges for data collection, analysis, and visualization in POE. This study aims to explore the applications of a BIM-IoT-GIS-integrated Digital twin for POE. First, high-level use case scenarios are developed to derive system requirements for a Digital twin platform. Second, four tests are conducted that provide a step-by-step procedure for BIM-IoT-GIS integration. Third, the integration is validated by geo-reference checks, data transfer checks, and visual checks. Based on the tests, a streamlined workflow is recommended for similar/future projects. The results demonstrate that Revit-ArcGIS Pro integration meets the system requirements for POE. Moreover, as shown in the graphical abstract (Figure 1 ), the spatial-temporal capabilities of ArcGIS Pro enable continuous monitoring and visualization of building performance in 4D. In conclusion, BIM-IoT-GIS integration can provide a solid foundation for developing a centralized digital twin for POE and enables researcher to collect and analyze the data without being physically present in the building.